Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. Size Order of Capitals of Kingdom of Saudi Arabia Regions, An Analytical Study through Modified Rank-size Rule according to 2022Prof. Mustafa Mohamed Ali Abbakar2. Quality of Life of Families of Persons with Sensory Disabilities: Problems and Adaption Mechanisms ResearchersMrs. Samaher Ahmad Al Ghamdi, Mrs. Reham Hassan Al Gurashi, Dr. Rajaa Taha Al Qahtani3. Empowerment of Women and Marital Harmony under Vision 2030: A Descriptive Study on the Empowerment of Women and Marital Harmony in the Kingdom of Saudi Arabia from the Perspective of Vision 2030Mrs. Safiah Mubarak Almaliki4. The most important common and different points between the motives of old and new atheismMrs. Al-Bandari Ganim Saad Al-Qahtani5. News treatment of the issue of terrorism on satellite channels: An applied descriptive study on the Qatari Al Jazeera channel in the period from May 2018 - May 2019Dr. Naglaa Hamdan Gadeen6. Recycling as a creative energy within the artwork formed with materials in Assemblage art - Kingdom Vision 2030Prof. Faten Mahmoud Suleiman Hilal7. Morphometric Analysis for Drainage Network of Yarmouk Basin in Jordan: A Study in Applied Geomorphology via Geographic Information System (GIS)Prof. Osama Abdullah Zairer
Keywords: Journal of Human and Social Sciences